2009
DOI: 10.1108/00346650910943299
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional quality of palm fat substituted chicken nuggets

Abstract: Purpose -The purpose of this paper is to improve the nutritional value of chicken nuggets by partial substitution of animal fat with palm stearin. Three nugget formulations with the fat level of 10.3 per cent palm fats consisted of blends from Olein: Stearin at ratios of 30:70, 50:50, 70:30 were used to replace chicken skin (control). Palm fat treatments resulted in a significant decrease of cholesterol content. Design/methodology/approach -Four nugget formulations with the fat level of 10.3 per cent palm fats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
5
2
Order By: Relevance
“…The study found the highest phosphorus concentration in citrus pulp, with a small amount also present in fruit skin. Our results related to phosphorus levels were higher than those reported by [30], who found 12 mg/100 g in oranges, 8 mg/100 g in grapefruit, and 16.2 mg/100 g in lemon. However, our findings differed from [26], who reported 181 mg/kg.…”
Section: Determination Of Mineralscontrasting
confidence: 91%
“…The study found the highest phosphorus concentration in citrus pulp, with a small amount also present in fruit skin. Our results related to phosphorus levels were higher than those reported by [30], who found 12 mg/100 g in oranges, 8 mg/100 g in grapefruit, and 16.2 mg/100 g in lemon. However, our findings differed from [26], who reported 181 mg/kg.…”
Section: Determination Of Mineralscontrasting
confidence: 91%
“…Besides that, Alina et al [4] reported that in chicken nuggets containing palm fat, they had harder texture compared to the control and commercial nugget samples and palm fat in the nuggets did not affect chicken flavor as perceived by consumers from the sensory evaluation scores. By using natural antioxidants, there is a potential advantage of reducing or replacing synthetic ones and reducing the production of off-flavours with a greater acceptance by the consumer [14].…”
Section: Introductionmentioning
confidence: 99%
“…Since chicken fat is high in unsaturated fats, it is easier to be oxidized [4]. Consequence of that, palm oils and red palm oils offer another alternative for animal fat replacement in meat products.…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional quality has been studied from multiple perspectives, namely quality (Huma et al , 2008), value (Alina et al , 2009; Hoefkens et al , 2009), nutrition content (Matthews et al , 2003), and the consequences when processing (Hunter, 1981). Huma et al (2008) investigated the effect of soaking and cooking on the anti‐nutrient contents and nutritional quality of the legumes.…”
Section: Nutritional Qualitymentioning
confidence: 99%
“…The results indicated that soaking and cooking of legumes significantly reduce their anti‐nutrients, namely phytic acid and tannin. Alina et al (2009) introduced how to improve the nutritional value of chicken nuggets by a partial substitution of animal fat with palm stearin. The results indicated that the texture of chicken nuggets increased when palm facts were added.…”
Section: Nutritional Qualitymentioning
confidence: 99%